KEABSAHAN JUAL BELI HAK ATAS TANAH BERDASARKAN HUKUM ADAT DI KECAMATAN BAKTIRAJA KABUPATEN HUMBANG HASUNDUTAN PROVINSI SUMATERA UTARA - ANDRIYANI NEHEMIA (jurnal.unprimdn.ac.id, 2020)
According the Batak adat (customary) law, the validity of transaction should meet three elements: in cash, real, and transparent. People in Baktiraja Sub-district still do land transaction based on adat law. It is made in a letter on embossed stamped paper signed by the seller and the buyer and witnessed by a village head although this method is rarely done today. The research problems are as follows: what factors which cause the implementation of land transaction is done based on adat law, how about the legality of land transaction based on adat law, and how about the resolution of any dispute in land transaction based on adat law in the people in Baktiraja Sub-district, Humbang Hasundutan Regency.The research used juridical empirical method. The data were obtained from primary, secondary, and tertiary legal materials. They were gathered by conducting library research and field research as well as interviews and analyzed qualitatively.The result of the research shows that some factors which cause land transaction is based on adat law in the people in Baktiraja Sub-district are legal factor since there is no PPAT (Official Empowered to Draw up Land Deeds) and non-legal factor since in tradition the implementation is easy, simple, and affordable. Land transaction in Baktiraja Sub-district is valid because it meets material requirement as it is specified in Article 1320 of the Civil Code. Any dispute in land transaction based on adat law in this Sub-district is resolved in a family manner.It is recommended that the Local Government provide counseling for the people about getting PRONA (Agrarian National Operation). The village heads should get involved in facilitating resolution in any disputes. The local people should do any land transaction in written forms.